2005
DOI: 10.1113/jphysiol.2004.081992
|View full text |Cite
|
Sign up to set email alerts
|

Early origins of obesity: programming the appetite regulatory system

Abstract: There is evidence that changes in perinatal nutrition programme the development of relative fat mass and the regulation of appetite in adult life. These studies have been primarily in the rodent utilizing maternal overnutrition or undernutrition imposed at different stages of pregnancy and beyond, mapping of neuropeptide localization and activity and appropriate null mutant models. Whilst the rodent offers significant advantages in terms of a short gestation and the availability of useful transgenic and null m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(145 citation statements)
references
References 102 publications
3
138
0
Order By: Relevance
“…Age at slaughter was similar for pigs from all treatment groups, although the pigs born to E sows were heaviest. This difference in weight may be explained by the trend towards higher growth rates, from birth to slaughter, of pigs born to E sows, suggesting that the growth of offspring may be programmed during early gestation (Barker, 1998;McMillen et al, 2005). Results of the current study also suggest that the programming of fat deposition may be influenced by the fatty acid profile of the maternal diet during early gestation, since the offspring of O sows were leaner at birth and at slaughter.…”
Section: --mentioning
confidence: 55%
See 1 more Smart Citation
“…Age at slaughter was similar for pigs from all treatment groups, although the pigs born to E sows were heaviest. This difference in weight may be explained by the trend towards higher growth rates, from birth to slaughter, of pigs born to E sows, suggesting that the growth of offspring may be programmed during early gestation (Barker, 1998;McMillen et al, 2005). Results of the current study also suggest that the programming of fat deposition may be influenced by the fatty acid profile of the maternal diet during early gestation, since the offspring of O sows were leaner at birth and at slaughter.…”
Section: --mentioning
confidence: 55%
“…Pigs from P dams also possessed more fat at 21 days of age, suggesting that they may have been programmed to lay down fat early in gestation (Barker, 1998;McMillen et al, 2005). Fat is lighter per unit volume than either bone or muscle, but is more energy dense.…”
Section: --mentioning
confidence: 99%
“…In addition to these age-dependent behavioral differences, the amount of food consumed during early rodent life plays an important role in determining subsequent food intake in later life (44). Following this initial observation, many studies have shown that postnatal nutrition is important for the regulation of appetite in adult rodents, suggesting that the energy balance is predominantly determined during early development (40).…”
mentioning
confidence: 99%
“…In ob/ob mice that are deficient in leptin neuronal projections from the ARC fail to develop normally, but can be rescued by neonatal but not adult administration of exogenous leptin (38) . In addition to the likely effect of early-life nutrition on the developing neuronal architecture of the hypothalamus, there is also evidence from rodents and sheep of functional imbalances in hypothalamic neuropeptide systems following early-life interventions (35,39,40) . Whereas the evidence for programming events as a consequence of maternal undernutrition is quite firm, there is also an emerging consensus that maternal hyperglycaemia and obesity, i.e.…”
Section: Early-life Programming Of Susceptibility To Obesitymentioning
confidence: 99%